Reduction of Nitrate Content in Baby-Leaf Lettuce and Cichorium endivia Through the Soilless Cultivation System, Electrical Conductivity and Management of Nutrient Solution - Conversa, Giulia; Bonasia, Anna; Lazzizera, Corrado; La Rotonda, Paolo; Elia, Antonio (Frontiers in Plant Science, 2021)
Soilless cultivation systems are efficient tools to control nitrates by managing nutrient solution (NS) salinity and nitrogen availability, however, these nitrate-lowering strategies require appropriate calibration based on species/genotype-specific responses interacting with climate and growing conditions. Three experiments were carried out on lettuce and Cichorium endive grown in ebb-and-flow (EF) and floating (FL) systems at two levels of NS salinity (EC=2.5 and 3.5 dS m-1) (EC2.5, EC3.5, respectively) under autumn and early-spring (lettuce) and winter and late-spring conditions (C. endive). Nitrogen deprivation (NS withdrawal a few days before the harvest) was tested at EC2.5, in the autumn and winter cycles. The EF-system caused an increase in salinity in the substrate where roots mainly develop so it mimicked the effect of the EC3.5 treatment. In the winter-grown lettuce, the EF-system or EC3.5 treatment was effective in reducing the nitrate level without effects on yield, with the EF baby-leaf showing an improved quality (color, dry matter, chlorophylls, carotenoid, vitamin C, phenol). In both seasons, the EF/EC3.5 treatment resulted in a decline in productivity, despite a further reduction in nitrate content and a rise in product quality occurring. This response was strictly linked to the increasing salt-stress loaded by the EC3.5/EF as highlighted by the concurrent Cl- accumulation. In early-spring, the FL/EC3.5 combination may represent a trade-off between yield, nitrate content and product quality. In contrast, in winter-grown endive/escarole the EC3.5, EF and EC3.5/EF reduced the nitrate level with no effect on yield, product quality or Cl- uptake, thus proving them to be more salt-tolerant than lettuce. High temperatures during the late-spring cycle promoted nitrate and Cl- uptake, overcoming the nitrate-controlling effect of salinity charged by the EF system or EC3.5. The nitrate level decreased after 3 day-long (lettuce) or 6 days-long (C. endive) NS withdrawal. In C. endive and EF-grown lettuce, it provoked a decrease in yield, but a concurrent improvement in baby-leaf appearance and nutritional quality. More insights are needed to fine-tune the duration of the NS removal taking into account the soilless system used and species-specific characteristics.